Investigating cart stacking as a response to free delivery thresholds in South African e-commerce - Mayaba, Yolisa (University of the Witwatersrand, Johannesburg, 2023)
The purpose of this study is to quantitatively investigate cart stacking as a response to the threshold for free delivery policy in South African e-commerce
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Contingent free shipping policy; Cart stacking; E - commerce; Pre intentioned cart; Threshold for free delivery policy; UCTD; SDG-8: Decent work and economic growth